Gendering criminology: crime and justice today - Clevenger, Shelly (Crime and justice today, 2021)
The story of gender : definitions, origins, and current issues -- The why and how : theories of gender, crime, and victimization -- "Manly" crimes : the relationship between masculinity and criminality -- "ladies only :" an examination of women and crime -- At the margins : criminalization within the LGBTQIA+ communities -- Gender-based online victimization -- "Boys will be boys" and "sugar and spice :" the relationship between gender and victimization -- The victimization of individuals who identify as LGBTQIA+ -- Policing crime : how gender influences arrest decisions and court cases -- The Gendered nature of punishment -- "Boys' club :" gender and employment in the criminal-legal system -- Gender, crime, and the media.